Winter male plumage coloration correlates with breeding status in a cooperative breeding species - Solís, Elena; Avilés, Jesús M.; de la Cruz, Carlos; Valencia-Ruíz, Juliána; Sorci, Gabriele (Oxford University Press, 2008)
The function of colored ornaments is usually related to the signaling of individual quality in intra- and intersexual interactions. In cooperative breeding species, where only a fraction of the male population access the breeding status and the other fraction has the option to help breeding pairs, colored traits might provide the females with a reliable information on the quality of potential mate. Males of the cooperative breeding azure-winged magpies (Cyanopica cyanus) display conspicuous blue plumage coloration. Here we explored the role played by structural blue coloration of males and the probability of becoming a breeder or a helper. Birds were trapped during 4 consecutive years, and feather coloration was measured with a spectrometer. Males that became breeders had a more brilliant and saturated blue coloration and showed a more violet hue in the nonbreeding period compared with birds that became helpers. Breeding males also showed a seasonal decline in blueness, whereas the color properties of helpers were constant throughout the year. Blueness of individuals trapped in the nonbreeding period was positively correlated with body size and condition. These findings are consistent with a scenario in which nonbreeding blue plumage coloration may function as a signal of individual quality in the azure-winged magpie at the pair formation time and add to growing evidence suggesting that the nonbreeding season appears particularly important in impacting breeding roles in cooperative breeding birds.
https://openpolicyfinder.jisc.ac.uk/id/publication/241
Keywords: Aves; Selección sexual en animales; Cooperative breeding; Cyanopica cyanus; Nonbreeding plumage; Sexual selection; Structural coloration